The legal mechanisms for the prevention of psychosocial risks at work: the implementation of the existing in search of renewal - Bouhlayes, Ilhem (Journal of Human Sciences, 2022)
The Algerian legislator, like comparative legislation, has put in place an employer protection system against occupational risks. The legal framework for this topic is reflected in the provisions of the 88-07 on health, safety and occupational medicine. this legislative text contains preventive measures such as joint committees, occupational medicine… According to this law, the notion of occupational health is quite vague which does not only mean physical health but also extends to moral health therefore; talking about occupational risks automatically includes psychological risks; say: Psychosocial risks, In this study we will begin the preventive provisions of occupational health and to what extent they represent a real challenge to deal with psychosocial risks.